2011
DOI: 10.1021/jp1108043
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of Metal (M = Au, Pt, Pd, or Ru) Bilayer Modified α-Fe2O3(0001) Surfaces

Abstract: Metal modified metal oxides are promising and economical catalysts for important processes such as CO oxidation and the partial oxidation of methanol. The present work is to investigate, by density functional theory, the electronic and geometric structures of metal (M = Au, Pt, Pd, or Ru) bilayer modified R-Fe 2 O 3 (0001) catalysts, focusing on the synergistic effect at the interface between the metal bilayer and R-Fe 2 O 3 (0001) support and its connection with its catalytic activity. It is found that the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 71 publications
5
24
0
Order By: Relevance
“…[11][12][13][14] The duration time for DNA chains passing through a nanopore is usually named as translocation time τ. In experiments, it was found that the translocation time can be governed by modifying the interactions between DNA chain and nanopore, 15,16 or changing the size of nanopore. 11,17 The translocation time is dependent on many factors such as polymer-pore interaction, [18][19][20] the solvent property, [21][22][23][24][25] pore size, 26 polymer-surface interaction, 27,28 chaperones and nanoparticles at the trans side.…”
mentioning
confidence: 99%
“…[11][12][13][14] The duration time for DNA chains passing through a nanopore is usually named as translocation time τ. In experiments, it was found that the translocation time can be governed by modifying the interactions between DNA chain and nanopore, 15,16 or changing the size of nanopore. 11,17 The translocation time is dependent on many factors such as polymer-pore interaction, [18][19][20] the solvent property, [21][22][23][24][25] pore size, 26 polymer-surface interaction, 27,28 chaperones and nanoparticles at the trans side.…”
mentioning
confidence: 99%
“…Translocation of NaPSS has been studied by several groups before [33][34][35]. In order to reduce the complexity in signal events [32], we chose a relatively short NaPSS sample (M w = 4300, M w /M n = 1.2) for translocation studies.…”
Section: Resultsmentioning
confidence: 99%
“…In principle, nanopores are also highly suitable for studying synthetic polyelectrolytes because they can also translocate through nanopores resembling DNA molecules. However, due to the molecular mass polydiversity and complicated sidechain structures of polyelectrolytes, only moderate successes have been achieved with nanopore sensors [32][33][34][35][36]. In this report, we propose to use a protein nanopore, ␣-hemolysin (␣HL), to investigate the effect of mono-and multivalent counterions on the conformational changes of a simple polyelectrolyte, sodium poly(styrenesulfonic acid) (NaPSS).…”
Section: Introductionmentioning
confidence: 99%
“…9 Since the first experiment on the translocation of DNA chain through a-hemolysin protein nanopores in 1996, 1 nanoporebased DNA sequencing has attracted increasing interest and great progress has been made during the last two decades. [10][11][12][13][14][15][16][17] The ionic current across protein nanopores or solid nanopores is reduced significantly when a polymer chain is inside the nanopore. 1,10,11,14 From the drop of the ionic current, one can measure the translocation time of a chain through nanopore.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] The ionic current across protein nanopores or solid nanopores is reduced significantly when a polymer chain is inside the nanopore. 1,10,11,14 From the drop of the ionic current, one can measure the translocation time of a chain through nanopore. 1 It was found that the level and shape of ionic current and the translocation time were dependent on the detailed information of DNA/RNA molecules when they were driven through the nanopore under external electrical potential.…”
Section: Introductionmentioning
confidence: 99%